Herbal formula xuling-jiangu improves bone metabolic balance in rats with ovariectomy-induced osteoporosis via the gut-bone axis - Chen, Juan; Ng, Szetuen; Xu, Pengchao; Chen, Sainan; Li, Shengqiang; Chen, Xuan; Xie, Lihua; Ge, Jirong (Frontiers in Pharmacology, 2024)
The XuLing JianGu recipe (XLJGR) is an empirical traditional Chinese medicine formula used for the treatment of osteoporosis. This study aimed to investigate the effects of XLJGR on the composition of intestinal microbiota and endogenous metabolites in ovariectomized (OVX) osteoporosis rats. An OVX rat model was established for intervention with XLJGR. Various measurements were taken, including bone mineral density, serum bone metabolism indicators, intestinal microbiota species and abundance, and changes in endogenous metabolites. Based on evidence from the literature, specific experimental conditions, including the dosage of XLJGR and the duration of intervention, were employed. Furthermore, differential metabolites were validated on MC3T3-E1 cells. The results demonstrated that XLJGR has the potential to modulate gut microbiota and influence the metabolism of endogenous compounds, thereby improving bone health. In conclusion, this study underscores the potential biomedical applications of XLJGR in promoting bone health, representing a viable alternative to existing therapeutics.